An Analysis Deixis in “Salt” Movie Script Directed by Phillip Noyce - Sitepu, Julyanta Br; Winarni, Winarni; Resmisari, Diah; Fasikh, mukhlasul; Murtadho, Abdul Muhid (STIBA IEC JAKARTA, 2025)
The objective of this research is to identify the types of deixis and the most dominant deixis in the SALT movie script directed by Philip Noyce. The study was conducted using a qualitative research method, focusing on the dominant deixis and its types in the script. The data collection process involved the following steps: first, the researcher watched the movie with English subtitles online; second, the movie script was obtained from the internet; then, the researcher categorized the various deixis in the script; and finally, the types of deixis were analyzed. The findings revealed several types of deixis in the script, including temporal, social, discourse, and spatial deixis, which encompass person and place deixis. Specifically, person deixis was the most prevalent, with 649 instances, accounting for 76 percent of the total. Within person deixis, first person deixis had 48 instances (7 percent), second person deixis had 279 instances (42 percent), and spatial deixis or place deixis had 66 instances (7 percent). Temporal deixis or time deixis had 29 instances (3 percent), social deixis had 24 instances (2 percent), and discourse deixis had 85 instances (10 percent). In total, 835 instances of deixis were identified in the script.